2021
DOI: 10.1186/s43159-021-00079-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Alvarado score and pediatric appendicitis score for clinical diagnosis of acute appendicitis in children—a prospective study

Abstract: Background Acute appendicitis is the most common surgical condition of children. Differential diagnosis of an acutely inflamed appendix in children includes a vast variety of diseases which can present with the same symptoms and signs as acute appendicitis. It is an important factor for delay in diagnosis. Many scoring systems are being used to reach a diagnosis within time and to reduce the rate of negative appendectomies. The purpose of this study was to compare both scoring s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A prospective study concluded that the PAS is superior to the Alvarado score in terms of diagnostic accuracy for pediatric appendicitis; therefore, it was used for this study. 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study concluded that the PAS is superior to the Alvarado score in terms of diagnostic accuracy for pediatric appendicitis; therefore, it was used for this study. 7…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study concluded that the PAS is superior to the Alvarado score in terms of diagnostic accuracy for pediatric appendicitis; therefore, it was used for this study. 7 The most common imaging modalities in the ED are ultrasound and CT scan. There is a concern for the liberal use of CT scans, especially in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many scoring systems for AA have been proposed and designed to aid the clinical assessment of patients and reduce the rate of negative appendectomies [ 2 , 9 ]. Some studies in the past showed that the evaluation of preoperative total white blood cell count in combination with neutrophils and C-reactive protein could reduce negative appendectomy rates from 24% to 16% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] The specificity of AS and PAS varies between 59%-72% and 50%-70%, respectively, while sensitivity varies between 76%-89% and 86%-93.8%, respectively. [7][8][9] Difficulties in diagnosing AA have led to increased search for biomarkers for a timely and accurate diagnosis. [10] Considering its etiopathogenesis as a vicious cycle of an immune response, comprising of infection, obstruction, and inflammation, researchers focused on investigating the immuno-inflammatory system components, i.e., white blood cells, interleukins.…”
Section: Introductionmentioning
confidence: 99%